Pemberdayaan Muallaf Perspektif Fikih Zakat; Studi Pemberdayaan Badan Amil Zakat Nasional - Waris Fahrudin (Universitas Wahid Hasyim Semarang, 2020)
Converts are a condition for muslims in the early days of studying Islamic teachings that require ongoing assistance and empowerment through formal institutions that are capable of actually providing assistance. In this case BAZNAS Temanggung Regency seeks to provide empowerment, especially for converts from Buddhism in Kaloran sub-district, Temanggung Regency, who have complex miniature religious treasures. This empowerment of converts becomes more interesting because it is viewed from the perspective of zakat fiqh so that it is known the perspective of shared in the aspect of the benefit of the people, especially for the mu'alaf from Buddhism in Kaloran District.This research is a field research with descriptive qualitative method in normative juridical approach. The aim is analyzing the problems of empowering converts from Buddhism by BAZNAS Temanggung Regency for the 2017-2019 period, and strategies for overcoming empowerment, as well as appropriateness from fiqh perspective.The research showed that the empowerment of Buddhist converts in Kaloran sub-district carried out by BAZNAZ Temanggung Regency in the perspective of zakat fiqh, it can be concluded that three main things, first the problem of BAZNAS Temanggung Regency 2017-2019 period in empowering converts from Buddhism in Kaloran sub-district are related to inadequate human resources. BAZNAS, weak organization, less than optimal distribution. The problems associated with converting to Islam are due to their dependent nature which results in their hopeful and lazy nature. Second, in dealing with these problems, the strategy adopted by BAZNAS in dealing with the problems of empowering converts from Buddhism and the positive impact felt by converts from Buddhism in form of strengthening human resources, strengthening organizational structure and increasing distribution so as to improve the quality of converts and reduce the dependency to be positive. In looking to the future. Third, there is compatibility in the perspective of zakat fiqh, and it is implemented in form of empowering converts from Buddhism by BAZNAS Temanggung Regency for the 2017-2019 period.